Genetic and phenotypic association between yield components in hybrid sorghum (Sorghum bicolor (L.) Moench) populations - Kenga, R.; Tenkouano, A.; Gupta, S.C.; Alabi, S.O. (Springer, 2006)
The magnitude of genetic expression and associations among traits are important for the prediction of response to selection in diverse environments and provide the basis for planning and evaluating breeding programs. In this regard, a cross classification mating design was used to produce hybrid sorghum populations, which were evaluated in a randomized completed block design with three replications at four environments in Northern Cameroon. Data on grain yield, days to anthesis, plant height, inflorescence length, threshing percentage and seed mass were collected and subjected to statistical genetic analyses. Significant genotype × environment interaction effects were observed for all traits. Genetic variance was essentially attributed to additive gene effects, with dominance variance for grain yield being negligible. However, the reverse was observed for threshability. Genetic variance components were much higher for plant height and grain yield than for days to anthesis, seed mass and threshability. Heritability estimates for plant height and inflorescence length were high (77 and 54 percent respectively) while the estimates for grain yield and threshability were low (14 and 5 percent respectively). Grain yield had positive genotypic correlation with most of the traits. Days to anthesis were negatively correlated with vegetative and reproductive traits. These results suggest that improvement of days to anthesis, plant height, and inflorescence length should be faster because of higher heritabilities and greater phenotypic variation. However, selection for earliness and reduced plant height would not be possible without hampering grain yield. Selecting for yield primary components namely inflorescence length and seed weight would be effective for increasing production. In addition, optimizing agronomic practices and improved experimental design would increase the selection efficiencies.